Outage analysis of industrial wireless networks: Efficient protocols and trade-offs - Zdravkovic, Nemanja (TELFOR : 2017 25th Telecommunication Forum : 21-22 November 2017, 2017)
This paper studies outage performance of decode-and-forward cooperative wireless networks subject to Nakagami-m multipath fading while set in an industrial environment, which requires low-latency and high reliability. Cooperating nodes communicate applying either a threshold-based or an Automatic Repeat reQuest (ARQ) protocol. Closed-form analytical expressions are derived when the network destination node applies maximal ratio combining, and are further verified through Monte Carlo simulations. The effects of type of protocol used, average signal-to-noise ratio values, network dimension and fading severity is discussed. Based on the presented results, the choice of internode protocol is considered a trade-off between the low-latency requirement and communication with no data loss.